ØªØ£Ø«ÙŠØ± Ù†Ù…ÙˆØ°Ø¬ ÙÙ‚Ù… ÙÙŠ ØªØØ³ÙŠÙ† Ù‚Ø¯Ø±Ø© Ù…Ù‡Ø§Ø±Ø© ÙƒÙ„Ø§Ù… ÙÙŠ Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø«Ø§Ù…Ù† Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø³Ø§ØªÙˆ Ø¢ØªØ§Ù Ù…Ø¹Ø±Ø§Ø¬ Ø§Ù„ØµØ¨ÙŠØ§Ù† Ù†Ù‡Ø¶Ø© Ø§Ù„ÙˆØ·Ù† Ø³ÙŠÙ„Ù†Ù„ÙŠØª - Muhammad Ihsan; Hardianti Sanusi (Lughatu Ad-dhat, 2023)
The learning model SEAL stands for active, creative, effective and fun learning. Do is a strategy that allows students to carry out various activities to develop their skills, attitudes and understanding with an emphasis on learning by doing. This study aims to determine the form of the application and the effect of the FEM model (Who Am I? (To enhance speaking skill. This research is a quantitative research (real experiment, ergonomic model) The game of Who am I? (Can have a positive and significant effect on the speaking skill in the Arabic language for eighth grade students in Sato Ataf Mearaj Secondary School Al-Subyan Nahdlat Al-Watan Silenlit in the academic year 2022 It should be Teachers are more creative in the learning process, not only focusing on the lectures, but also being able to make a bored class always active and enthusiastic in the learning process.